Guidelines for consistent cardiovascular post-mortem examination, sampling and reporting of lesions in European zoo-housed great apes - Strong, Victoria; Sheppard, M.N; Redrobe, Sharon; Baiker, Kerstin (Wiley, 2018)
Inconsistencies and inadequacies in both the approach to post-mortem examination of the heart and the subsequent reporting of findings have been blamed for a lack of progression of understanding about great ape cardiovascular disease. In order to minimize and confront these issues in the United States, Association of Zoos and Aquariums-member zoos have necropsy data collated by the Great Ape Heart Project using a protocol developed by their pathology advisors. In Europe, however, there does not appear to be in existence any standardization or process for consistent cardiac post-mortem examination, data collection and/or relevant research. This article provides those readers working within/for European collections with a suggested protocol for the initial post-mortem inspection and sampling of the hearts of great apes. This article also outlines the detailed macroscopic and histopathological examination that is currently carried out at The University of Nottingham, UK, as part of an ongoing prospective, multi-centre study into great ape cardiovascular disease aetiopathogenesis. Finally, readers are offered guidance on the reporting and description specifically of idiopathic myocardial fibrosis (also referred to elsewhere as fibrosing cardiomyopathy). The standardized post-mortem examination of the great ape heart across European zoological collections will ensure a more uniform sampling procedure resulting in the availability of consistent good-quality data. It is hoped that this will, in turn, inform diagnostic pathology and research in this area, and enhance understanding about the aetiopathogenesis of great ape cardiovascular lesions.